Environmental Concern and Purchase Intention of Electric Vehicles in the Eastern Part of China - Moyo, Ngqabutho (Archives of Business Research, 2018)
The main objective of this research was to examine the effects of environmental concern on the purchase intention of electric vehicles in the eastern part of China. The research adopted a qualitative approach to elicit data from a sample of 86 participants living in Beijing. Stratified random sampling was used as a sampling technique for these participants. The research findings indicate that environmental concern plays a significant influential role in the purchase decision of electric vehicles. The findings reflect that consumers who are environmentally concerned are more willing to purchase electrical vehicles as a means to protect their environment from air pollution. Several types of environmental concern or value orientations and their effects on the purchase decision of electric vehicles were also examined. Egoistic, social-altruistic and biospheric values were identified as the most influential value orientations in the purchase intention of electric vehicles. Apart from environmental concern and its value orientations, the study also found out that the purchase decision of electric vehicles is also affected by factors such as government incentives or subsidies on electric cars, reference group or peer group influence, driving range, possible top speed, cost of the vehicle itself, battery capacity, battery life, and charging time, appearance, charging stations, vehicle performance, maintenance costs and vehicle safety, lack of choice in vehicles, lack of electric vehicle infrastructure and potential increases in electric rates. It is therefore recommended that these factors are addressed in order to enhance the attractiveness of electric vehicles. More importantly, environmental concern has to be reinforced through campaigns which are focused on raising awareness on the issue of environmental sustainability.